Associations between LGBTQ-affirmative school climate and adolescent drinking behaviors. (1st April 2016) - Coulter, Robert W.S.; Birkett, Michelle; Corliss, Heather L.; Hatzenbuehler, Mark L.; Mustanski, Brian; Stall, Ron D.
Highlights: We investigated associations between LGBTQ school climates and adolescent drinking. LGBTQ school climate was associated with adolescent drinking behaviors. Gays/lesbians had fewer heavy episodic drinking days in more affirmative climates. Heterosexuals had fewer heavy episodic drinking days in more affirmative climates. Abstract: Background: We investigated whether adolescents drank alcohol less frequently if they lived in jurisdictions with school climates that were more affirmative of lesbian, gay, bisexual, transgender, and questioning (LGBTQ) individuals. Methods: Data from the 2010 School Health Profile survey, which measured LGBTQ school climate (e.g., percentage of schools with safe spaces and gay-straight alliances), were linked with pooled data from the 2005 and 2007 Youth Risk Behavior Survey, which measured sexual orientation identity, demographics, and alcohol use (number of drinking days, drinking days at school, and heavy episodic drinking days) in 8 jurisdictions. Two-level Poisson models tested the associations between school climate and alcohol use for each sexual-orientation subgroup. Results: Living in jurisdictions with more (versus less) affirmative LGBTQ school climates was significantly associated with: fewer heavy episodic drinking days for gay/lesbian (incidence-rate ratio [IRR] = 0.70; 95% confidence interval [CI]: 0.56, 0.87; p  = 0.001) and heterosexual (IRR = 0.80; 95% CI: 0.76, 0.83; p  < 0.001) adolescents; and fewer drinking days at school for adolescents unsure of their sexual orientation (IRR = 0.57; 95% CI: 0.35, 0.93; p  = 0.024). Conclusions: Fostering LGBTQ-affirmative school climates may reduce certain drinking behaviors for gay/lesbian adolescents, heterosexual adolescents, and adolescents unsure of their sexual orientation.